Global Versus Domain-Specific Identity Processes: Which Domains Are More Relevant For Emerging Adults?. Issue 1 (February 2018) - Vosylis, Rimantas; Erentaitė, Rasa; Crocetti, Elisabetta
The current study contributes to the ongoing discussion about validity and utility of global and domain-specific assessment of identity processes in emerging adulthood (EA) by using a three-dimensional model of identity development and examining four identity domains (best friend, education, occupation, and partner). The links between global and domain-specific identity processes and main features of EA are analyzed in the Eastern European context, which is largely underrepresented in studies on identity development. Participants were 1, 217 (49.9% females) emerging adults aged between 20 and 31 years ( M age = 25.89, SD age = 3.51). This study showed that global identity processes only partly explain domain-specific ones and that domain-specific processes have unique links with features of EA. Taken together, this study shows that consideration of different life domains to measure identity processes is essential, since identity development in friendship, partnership education, and work domains can have different associations with outcomes of interest.